O custo da responsabilidade social dos hospitais filantrópicos - Ferrer, Francisco Roso (Universidade do Vale do Rio dos Sinos, 2016)
Social responsablidade of Philanthropic Hospitals comes from their stories, since many of these institutions will have their origin related to the philanthropy of its pecursores. This article aims to analyze the management of the social responsibility of a philanthropic Hosptal of Rio Grande do Sul, the Our Hospital Lady of Pompeii, as well as presenting the origin of the essential financial resources in the composition of the institution's revenues and demonstrate their operational cost. The approach is qualitative in nature and as a research strategy was the case study used. For data collection were carried out studies of the reports of the Financial and Hospital Billing sectors. It also analyzed the relevant legislation to the case. Thus, the Philanthropic hospitals work assisting the state in meeting the population seeking care through the National Health System. Therefore the proceeds from the public spheres are important to hospitals do their duty.
Keywords: Responsabilidade social; Sistema único de saúde; Custo; Social responsibility; Health system; Cost